1975
DOI: 10.1136/jnnp.38.10.977
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar hypoventilation and hyperosmnia in myotonic dystrophy.

Abstract: SYNOPSIS A case of myotonic dystrophy accompanied by alveolar hypoventilation and hypersomnia is presented. Radiological studies and EMG examination of the intercostal muscles demonstrated that the respiratory muscles were affected by the disease, while polygraphic recordings showed that the alveolar hypoventilation and pulmonary hypertension worsened during sleep. The hypersomnia preceded the appearance of clinical signs of the muscular disease by many years and persisted even after treatment when the blood g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
1
1

Year Published

1978
1978
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(50 citation statements)
references
References 18 publications
5
43
1
1
Order By: Relevance
“…56 In patients with end-stage disease, degeneration of oropharyngeal, intercostals, and diaphragm muscles may lead to obstructive sleep apnea and nocturnal alveolar hypoventilation. 18,19 There is evidence that excessive daytime sleepiness in DM1 is not the result of sleep apnea 124 but may result from direct involvement of bulbar neurons in the reticular formation of the brainstem. 81,82 Broughton et al 10 concluded that cognitive impairment cannot be attributed to a secondary effect of nocturnal sleep apnea or sleep disturbance in patients with DM1, but probably represents a direct effect of CNS lesions.…”
Section: Global Intelligencementioning
confidence: 99%
“…56 In patients with end-stage disease, degeneration of oropharyngeal, intercostals, and diaphragm muscles may lead to obstructive sleep apnea and nocturnal alveolar hypoventilation. 18,19 There is evidence that excessive daytime sleepiness in DM1 is not the result of sleep apnea 124 but may result from direct involvement of bulbar neurons in the reticular formation of the brainstem. 81,82 Broughton et al 10 concluded that cognitive impairment cannot be attributed to a secondary effect of nocturnal sleep apnea or sleep disturbance in patients with DM1, but probably represents a direct effect of CNS lesions.…”
Section: Global Intelligencementioning
confidence: 99%
“…However, the ptosis, myopathic facies and dysarthric speech noted in DM can give a false impression of somnolence, and therefore the true extent of the problem could be overestimated. A variety of factors including affective state, respiratory [8][9][10][11][12][13][14] and generalised skeletal muscle weakness, abnormalities in central and peripheral respiratory control [10,13,[15][16][17][18] and in arousal [19][20][21][22] might be associated with sleepiness in DM. Somnolence is recognised as a symptom which causes significant disability and handicap in the general population [23].…”
mentioning
confidence: 99%
“…tilation. 13,14 Several lines of evidence suggest that DM1 may also have direct effects on sleep regulatory circuits in the CNS. [15][16][17][18][19][20][21][22] Narcolepsy is associated with decreased levels of hypocretin 1 (Hcrt-1) in the CSF and loss of Hcrt-1-releasing neurons in the dorsolateral hypothalamus.…”
mentioning
confidence: 99%